Sex differences in the associations between right heart structure and peak exercise capacity parameters in amateur cyclists - Pytka, Michał Jakub; Domin, Remigiusz Andrzej; Żołyński, Mikołaj Stanisław; Niziński, Jan; Krauze, Tomasz; Wykrętowicz, Andrzej; Guzik, Przemysław (Frontiers in Physiology, 2024)
Right heart changes and their association with exercise capacity, including sex differences, are still being investigated. We analysed right heart structure and its relationship with exercise capacity parameters in amateur cyclists.A cross-sectional study involving 215 consecutive adult amateur cyclists, who underwent resting transthoracic echocardiography and cardiopulmonary exercise testing (CPET) to exhaustion was performed.The median age of participants was 29 years (IQR 24-37), 71% of them were men. The mean training time was 6 hours/week, and 90% participated in vigorous or moderate physical activity. Men had larger right ventricular diameters (basal -RVD1, mid-cavity -RVD2 and longitudinal -RVD3) compared to women (40.9 vs 37.6 mm, p=0.0005, 28.7 vs 26.3 mm, p=0.03, 92.2 vs 81.9 mm, p<0.0001). Indexing for body surface area revealed comparable right atrial volume (RAVI) between sexes (24.1 vs 22.7 mL/m 2 ). Men achieved higher peak exercise capacity parameters [O2 pulse, oxygen consumption (VO2) and workload] in CPET. Multivariate linear regression models revealed a positive association between peak VO2, workload and O2 pulse with RAVI in women but not with RVD1 or RVD3. Conversely, these parameters showed a positive association with RVD3 and RVD1 but not with RAVI in men.Sex differences exist in the relationship between right heart structural parameters and peak exercise capacity descriptors in amateur cyclists. Better exercise capacity during CPET to exhaustion is associated with greater RAVI in women but a greater RVD1 and RVD3 in men. These findings suggest different mechanisms of right heart adaptation to training in men and women.